Early Antibody Dynamics in a Prospective Cohort of Children At Risk of Celiac Disease. (20th March 2023) - Valitutti, Francesco; Leonard, Maureen M.; Kenyon, Victoria; Montuori, Monica; Piemontese, Pasqua; Francavilla, Ruggiero; Malamisura, Basilio; Norsa, Lorenzo; Calvi, Angela; Lionetti, Maria Elena; Baldassarre, Mariella; Trovato, Chiara Maria; et al.
Abstract : INTRODUCTION: The purpose of this study was to identify possible serum biomarkers predicting celiac disease (CD) onset in children at risk. METHODS: A subgroup from an ongoing, international prospective study of children at risk of CD was classified according to an early trajectory of deamidated gliadin peptides (DGPs) immunoglobulin (Ig) G and clinical outcomes (CD, potential CD, and CD autoimmunity). RESULTS: Thirty-eight of 325 children developed anti-tissue transglutaminase IgA antibody (anti-tTG IgA) seroconversion. Twenty-eight of 38 children (73.6%) showed an increase in anti-DGPs IgG before their first anti-tTG IgA seroconversion. DISCUSSION: Anti-DGPs IgG can represent an early preclinical biomarker predicting CD onset in children at risk.